Experiential Learning With Continuous Glucose Monitors: A Novel Curriculum for Volunteers in a Student-Run Free Clinic - Annie E Altman-Merino; Shreyas G Krishnapura; Sachin K Aggarwal; Christopher Terry; Jordan Wright; Eleanor O Weaver; Babatunde Carew; Robert F Miller; Marguerite Cooper Lloyd (Journal of Student-Run Clinics, 2024)
Background: Growing evidence suggests that medical students and faculty preceptors have limited familiarity with continuous glucose monitors (CGMs), which may negatively affect how care teams counsel patients and monitor the use of CGMs. Although studies have shown that structured training for care teams may improve knowledge and comfort with various healthcare tools, to our knowledge, no study has attempted to do so for CGMs.Methods: We designed a user experience course for medical students and faculty mentors to address this gap at a student-run free clinic. This course allowed twenty participants to wear a CGM for two weeks and participate in three interactive didactic sessions and group reflections. We evaluated how knowledge and comfort with CGMs among participants changed after the course with a survey and focus group.Results: The cohort showed improvement in self-reported confidence in using the device, teaching patients how to use the device, and interpreting data (p<0.001). The majority of participants demonstrated improvement across all survey domains with higher post-intervention scores than pre-intervention scores. Qualitative analysis of group reflections elucidated three primary themes across participant experiences: the emotional impact of wearing the device, attitude changes with prolonged use, and behavior modification in response to glucose data.Conclusion: This novel educational initiative may improve knowledge about CGMs, ability to counsel patients to use the device, and understanding patients' experiences among medical students and faculty mentors. We plan to expand this educational opportunity to additional clinic volunteers, include patient perspectives, and share the curriculum with other student-run clinics.